The end of abundance : economic solutions to water scarcity - Zetland, David (Amsterdam ; Mission Viejo : Aguanomics Press, 2011)
"An analysis of how management institutions may fail to cope with freshwater scarcity and how to reform them" -- Provided by publisher.
Prologue -- The beginning of the end -- Part I: Personal water choices: 1. Water from the tap -- 2. Dirty water -- 3. The liquid lifestyle -- 4. Water for profit -- 5. Food and water -- 6. Water for power for water -- Part II: Social water choices: 7. Managers and politicians -- 8. Dams, pipes and pumps -- 9. Water and the environment -- 10. Weather and climate change -- 11. A human right to water -- 12. Water wars -- Afterword: What you can do.
Includes bibliographical references (p. 259-275) and index.
Keywords: Water resources development -- Economic aspects; Water resources development -- Government policy